Strategic Management and Competitive Advantage of Microenterprises in the Province of Batangas, Philippines - O. Lopez, Mabel (Journal of Technology Management and Business, 2023)
Increasing competitive pressures from a highly competitive global economy are forcing microenterprises to reevaluate their strategic position. Hence, adopting and implementing strategic management techniques enable them to respond proactively to change, leading to competitive advantage. This study examines strategic management and its relationship to the competitive advantage of microenterprises. This study surveyed 331 microenterprises in the province of Batangas in the Philippines. The data were analysed using descriptive statistics, correlation analysis, and focus group discussions. The results showed that most microenterprises need a written business plan, communicate and assign people to implement the strategy, and offer incentives or rewards to employees. They also need to improve in selling low-cost products, collaborating with business partners, and expanding to other locations.